2018
DOI: 10.15381/rivep.v29i3.13898
|View full text |Cite
|
Sign up to set email alerts
|

Mascotas silvestres en la práctica veterinaria de Guatemala

Abstract: El médico veterinario de especies menores se enfrenta, a menudo, con el reto de atender pacientes silvestres. Esta situación requiere que los clínicos de animales de especies menores tengan competencias y conocimientos especiales que les permitan resolver los casos. Con el objeto de generar información sobre las especies silvestres que son llevadas a las clínicas veterinarias en Guatemala, se realizó una encuesta de opinión a médicos veterinarios que practican la clínica de especies menores. Participaron 143 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Other geographical contexts have also assessed the implementation of zoological medicine and the work with exotic animals and NTCAs. For instance, a study conducted in Guatemala in 2018 revealed the lack of confidence that most veterinarians surveyed have when they must work with wild and exotic animals; even though they indicated that 92.3% were directly attended to and treated, only 5.6% were referred to another clinic, and 2.1% were not attended [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other geographical contexts have also assessed the implementation of zoological medicine and the work with exotic animals and NTCAs. For instance, a study conducted in Guatemala in 2018 revealed the lack of confidence that most veterinarians surveyed have when they must work with wild and exotic animals; even though they indicated that 92.3% were directly attended to and treated, only 5.6% were referred to another clinic, and 2.1% were not attended [ 36 ].…”
Section: Resultsmentioning
confidence: 99%